112 Impact of the COVID-19 pandemic on emergency department visits at a university medical centre. (29th October 2021) - Mallette, Viviane; Cyr, Claude
Abstract: Primary Subject area: Emergency Medicine - Paediatric Background: The new coronavirus, SARS-Cov-2, responsible for a global pandemic, led to the declaration of a health emergency and the implementation of large-scale public health measures by governments in 2020. Those measures, combined with the overlapping symptoms of COVID-19 disease and common viral infections in children, have led hospitals to prepare for possible changes in volume of emergency room visits by children. Objectives: This study aims to determine the effect of the pandemic and governmental restrictions on the use of the emergency department by pediatric patients at a university medical centre, as well as to assess the impact on the severity of initial presentations. Design/Methods: A single-centre study was conducted at a university hospital among children aged 0 to 17 who visited the emergency room. We used interrupted time series analysis to compare the average of pre-COVID-19 data (from January 1 2017, to December 31 2019) with data from the first wave of the COVID-19 pandemic (from January 1 to September 2020). Emergency room visits, initial triage codes, and admission and pediatric consultation rates were analyzed to assess whether there was a significant difference between periods. Results: An important increase in total daily visits (+11.18, 95% CI [6.23-16.14]) was first observed with the emergence of COVID-19 cases in Canada. Then, during the strict confinement, which corresponds to an active period of COVID-19, we detected a significant drop in daily visits (-25.64, 95% CI [-30.4 to -20.66]), which continued while progressively loosening restrictions. The proportion of admissions and pediatric consultations rose slightly only throughout the time of intensive health measures (respectively +4.07% and +3.32%), but no changes in the severity of the triage codes at the emergency department were observed for all periods. Traumatic injuries also saw a significant decrease (p=0.018) when comparing data by groups of diagnosis. Conclusion: These results show a significantly lower number of children's visits to the emergency room of a university medical centre, and a transient increase in pediatric care with little impact on the immediate severity of the initial presentations during strict government health measures in the first wave of COVID-19. These measures also had a beneficial effect in reducing the number of traumatic injuries.